If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -5(4 + -5x) = -67 3 + (4 * -5 + -5x * -5) = -67 3 + (-20 + 25x) = -67 Combine like terms: 3 + -20 = -17 -17 + 25x = -67 Solving -17 + 25x = -67 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '17' to each side of the equation. -17 + 17 + 25x = -67 + 17 Combine like terms: -17 + 17 = 0 0 + 25x = -67 + 17 25x = -67 + 17 Combine like terms: -67 + 17 = -50 25x = -50 Divide each side by '25'. x = -2 Simplifying x = -2
| 16=4(8-z)2 | | 119-3x=15x+1 | | 9x+27=41+2x | | 8x+22=52-2x | | -3-6x=4x+23 | | 3x-1=2x-5 | | 10x+7=5x-14 | | 10x-190=10x+190 | | 7+7x=49+x | | 0.5x+0.5=11.5 | | 0.6x+0.5=11.5 | | 5(x-2)+3x= | | 7-2(5-2x)= | | 3(x+2)+4(x-5)= | | a-5+2a-8a=5 | | 2(x+3)-4x=5x-(3x-12)+8 | | 3x+4y=125 | | -3(x-5)=4x+5 | | y+.1=-22.4 | | 5(2x-3)+4(x+1)= | | 2(5p-q)-(p-3q)= | | y+0.11=-22.4 | | X*(X-3)=42 | | 5x-25-8x=3-8x+2x | | -4g=-28 | | w+27=81 | | x^3+4x^2-12x+4=0 | | 18=x-6 | | 7x-2(4x+8)=-x-16 | | 5(a-b)+6(a+b)-7(a-2b)= | | 7(x-1)-2(x+1)+3(x-4)= | | 4(6-2x)-3(3-4x)= |